Development of broadband ultraviolet pulsed laser using Ce:LiCAF crystal to determine SO\(_2\) gas concentration by differential absorption spectroscopy - Pham, Minh Hong; Nguyen, Diep Van; Pham, Duong Van; Nguyen, Tu Xuan; Do, Hieu Minh; Doan, Kieu Anh Thi; Phung, Tiep Viet; Luu, Hong Dang; Le, Dang Van; Vu, Bich Thi; Cadatal-Raduban, Marilou; Dinh, Trung Van (Communications in Physics, 2024)
Earth’s atmosphere is a mixture of many gases which include pollutants such as SO2, NO2, NO, and O3 that have absorption  in the ultraviolet (UV) wavelength region. Therefore, the development of  broadband UV laser sources that are useful in a differential absorption spectroscopy (DOAS) system for environmental research is necessary. In this research, we present the DOAS system using the Ce:LiCAF laser for determining SO2 gas concentration in the atmosphere. The Ce:LiCAF laser has a full width at half maximum of 2 nm with a wavelength range from 286 to 291 nm and a peak wavelength of 288.5 nm. The results show that the DOAS system accurately determines the gas concentration with a measurement error of 6 %. This result can serve as the basis for developing practical DOAS systems with the ability to monitor a wide range of gasses and survey many other types of pollutants.